Pengembangan Bahan Ajar Mata Pelajaran Fiqih Berbasis Multimedia untuk Meningkatkan Minat Belajar Siswa Kelas VIII di MTs Putri Ma’arif Ponorogo - Mita Siti Afifah Mita Afifah (Social Science Academic, 2023)
Problems in learning islamic religious education can occur anytime and anywhere, both in public schools and in private schools. In some educational institutions, pai learning is usually still dominant using the lecture method. This is due to the age of the teacher who is not classified as young, so students feel bored and sometimes even sleepy when learning pai is carried out. This is what sometimes makes students less interested in learning pai. From some of these problems the author seeks to provide related to the development of multimedia-based fiqh teaching materials to increase class student interest in mts putri ponorogo. The results of this study were that when pai learning was carried out in class using the media that had been prepared, all students seemed enthusiastic and very enthusiastic about participating in the learning process. Students also don't feel bored because it is equipped with interesting pictures and sounds. Keywords: interactive multimedia, interest in learning